2020
DOI: 10.2147/ott.s208024
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA Profile Identifies miR-6165 Could Suppress Gastric Cancer Migration and Invasion by Targeting STRN4</p>

Abstract: Background: Recent studies showed that aberrant expression of miRNAs causes tumorsuppressing or promoting effects in various cancers including gastric cancer (GC). Our previous studies showed that lots of miRNAs and mRNA expressed differentially in GC and normal tissues. However, the critical miRNAs and mRNA need to be clarified. Materials and Methods: Microarray sequencing was used to profile the differential expression of miRNAs and mRNA in GC and normal tissues. Bioinformatics analysis and database predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…miR‐6165 is predicted to be a target of circ_0001459. miR‐6165 can inhibit the migration and invasion of gastric cancer by regulating STRN4 11 . miR‐6165 is a tumor suppressor in colorectal cancer that can regulate IGF1R expression 12 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…miR‐6165 is predicted to be a target of circ_0001459. miR‐6165 can inhibit the migration and invasion of gastric cancer by regulating STRN4 11 . miR‐6165 is a tumor suppressor in colorectal cancer that can regulate IGF1R expression 12 .…”
Section: Discussionmentioning
confidence: 99%
“…miR‐6165 can inhibit the migration and invasion of gastric cancer by regulating STRN4. 11 miR‐6165 is a tumor suppressor in colorectal cancer that can regulate IGF1R expression. 12 The close interaction between miR‐6165 and circ_0001459 was confirmed in HCC cells; miR‐6165 inhibitor was found to reverse the functional changes in HCC cells caused by circ_0001459 knockdown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SMAGP encodes a transmembrane glycoprotein that plays an important role in tumor invasion and metastasis ( 45 47 ). STRN4 belongs to the striatin family and functions as a co-factor ( 48 ), particularly in cancer-related pathways ( 49 ) in prostate ( 50 ), lung ( 51 ), and gastric ( 52 ) cancers. In the current study, ZNF540 and SMAGP were identified as prognostic markers for LUAD for the first time, but their specific roles and potential regulatory mechanisms require further investigation.…”
Section: Discussionmentioning
confidence: 99%